2016
DOI: 10.21082/ijas.v9n2.2008.68-76
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination on Corn Used by Feed Mills in Indonesia

Abstract: Mycotoxins which are secondary metabolites of fungi contaminate agricultural products such as corn and have deleterious effects on human and animal. The objective of this study was to evaluate the mycotoxin contamination on local and imported corn samples collected from different feed mills in Indonesia. Three hundred fifty six of corn samples (0.50 kg each) were sent by several feed mills to the Indonesian Research Institute for Animal Production during [2005][2006]. The background information accompanied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…The study showed a high occurrence of contamination in complete feed, dried fish and rice hulls (100%) with an average contamination of 0.03 mg/kg or exceeding the threshold limit of 0.02 mg/kg for duck feed. The contamination of several mycotoxins was previously reported by [9] on maize from Indonesia, USA and Argentina. The results showed that Aflatoxin was the most common mycotoxin found in the corn, with 47% of the local corn samples exceeding the Indonesian Standard of Industry (0.05 mg/kg).…”
Section: The Occurrence Of Mycotoxinmentioning
confidence: 62%
“…The study showed a high occurrence of contamination in complete feed, dried fish and rice hulls (100%) with an average contamination of 0.03 mg/kg or exceeding the threshold limit of 0.02 mg/kg for duck feed. The contamination of several mycotoxins was previously reported by [9] on maize from Indonesia, USA and Argentina. The results showed that Aflatoxin was the most common mycotoxin found in the corn, with 47% of the local corn samples exceeding the Indonesian Standard of Industry (0.05 mg/kg).…”
Section: The Occurrence Of Mycotoxinmentioning
confidence: 62%
“…For instance, maize for feed manufacture in Indonesia was separated into three grades of decreasing quality before being analysed for aflatoxin contents. The quality of the maize was determined visually on the basis of the proportions of foreign materials and mouldy, dead, or damaged kernels, as per the Indonesian grading system routinely practiced by the feed milling industry [161]. Unexpectedly, the results showed that aflatoxin concentrations increased from the best to the worst grade of the grains, suggesting that the grading system relying on visual inspection does not reflect a priori extent of contamination.…”
Section: Feed Contaminationmentioning
confidence: 99%
“…For instance, maize for feed manufacture in Indonesia was separated into three grades of decreasing quality before being analysed for aflatoxin contents. The quality of the maize was determined visually on the basis of the proportions of foreign materials and mouldy, dead, or damaged kernels, as per the Indonesian grading system routinely practiced by the feed milling industry [173]. Unexpectedly, the results showed that aflatoxin concentrations increased from the best to the worst grade of the grains, suggesting that the grading system relying on visual inspection does not reflect a priori extent of contamination.…”
Section: Feed Contaminationmentioning
confidence: 99%